2020
DOI: 10.1103/physrevmaterials.4.113610
|View full text |Cite
|
Sign up to set email alerts
|

Switching friction at a manganite surface using electric fields

Abstract: We report active control of the friction force at the contact between a nanoscale asperity and a La0.55Ca0.45MnO3 (LCMO) thin film using electric fields. We use friction force microscopy under ultrahigh vacuum conditions to measure the friction force as we change the film resistive state by electric field-induced resistive switching. Friction forces are high in the insulating state and clearly change to lower values when the probed local region is switched to the conducting state. Upon switching back to an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…In this section, we quantitatively compare the analytic expressions in Eq. (19) with the numerical data obtained in simulations, in the limit of 𝜔 → 0.…”
Section: Theory and Simulation: Quantitative Comparisonmentioning
confidence: 78%
See 2 more Smart Citations
“…In this section, we quantitatively compare the analytic expressions in Eq. (19) with the numerical data obtained in simulations, in the limit of 𝜔 → 0.…”
Section: Theory and Simulation: Quantitative Comparisonmentioning
confidence: 78%
“…An AFM tip sliding over a surface is known to perform so-called slip-stick motion [1][2][3][4][5][6][7][8], most naturally understood from the famous Prandtl-Tomlinson model [1,2]. A related question concerns the energy dissipation channels in such a sliding process; contributions have been found from electrostatic interactions [9][10][11], electron excitation on the conduction band [9,12,13], and phonon dynamics [9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. More specifically, energy transport by phonons has been conjectured to be responsible for remarkable properties in friction, e.g., in polaronic conductors, where a drastic increase of friction near a phase transition was observed [19,20], or in super conductors [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 46–50 ] In addition to allowing systematic tests of the effects of electronic, magnetic, and phononic degrees of freedom on friction, the manganite films offer potential technological application since it has recently been shown that resistive switching of manganite films offers a practical tactic for controlling friction without having to vary the temperature. [ 54 ]…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49][50] In addition to allowing systematic tests of the effects of electronic, magnetic, and phononic degrees of freedom on friction, the manganite films offer potential technological application since it has recently been shown that resistive switching of manganite films offers a practical tactic for controlling friction without having to vary the temperature. [54] A 6 nm thick film of La 0.7 Sr 0.3 MnO 3 (x = 0.3 specimen) was fabricated on a buffered SrTiO 3 substrate by metal-organic aerosol deposition, [55] with a FM-PM transition at T C = 338 K and a metal-like to hopping small polaron conductivity transition at T MM = 330 K. A 70 nm thick film of La 0.8 Sr 0.2 MnO 3 (x = 0.2 specimen) was fabricated on SrTiO 3 by sputter deposition and exhibits a FM-PM transition at T C = 220 K and a metal-polaronic conductor transition at T MM = 187 K. The crystal structure is rhombohedral both above and below the transitions (R3c space group) and strained due to the epitaxial relation with the underlying substrates. [51] Measurements to determine crystal structure, film thickness, magnetic properties, and resistivity are summarized in the Supporting Information for both films (Figures S1-S10, Supporting Information).…”
Section: Friction and Adhesion Forces At The Phase Transitionmentioning
confidence: 99%